Avrupa tarihinden kesitler 1789-1980 - Lee, Stephen J.; Aktur, Savaş; Dost Kitabevi (Ankara : Dost, 2004)
Discusses topics in European history, covering a period that ranges from the Renaissance to the onset of the French Revolution.
Includes bibliographical references.
Turkish.
Keywords: Europe -- History -- 1789-1980.; France -- History -- Revolution